GENETIC MUTATIONS IN INFLUENZA VIRUS AND THEIR IMPACT ON ANTIVIRAL TREATMENTS: A THEORETICAL ANALYSIS - Obeed, Ameer Najy; Aziz, Zainab Nadhum; Al-Waeli, Jaafar Hamid Jaafar (Journal of Medical Genetics and Clinical Biology, 2026)
Objective: This study synthesizes recent evidence (2020–2025) to evaluate key influenza virus mutations associated with resistance to neuraminidase inhibitors (oseltamivir, zanamivir) and cap-dependent endonuclease inhibitors (baloxavir), and to assess their implications for antiviral efficacy. Method: A structured literature analysis was conducted by integrating global surveillance reports and peer-reviewed studies, summarizing mutation frequencies and resistance patterns, supported by descriptive statistical tabulation and simulated trend visualization. Results: The findings indicate that canonical neuraminidase resistance mutations such as H275Y, R292K, and N295S remain rare, generally occurring at <1% prevalence across most surveillance datasets, although localized increases in PA-I38 substitutions associated with reduced baloxavir susceptibility have emerged in specific regions. The theoretical impact assessment suggests that resistance-linked mutations primarily reduce clinical effectiveness in post-treatment isolates and in severe or immunocompromised cases. Novelty: This work provides an updated synthesis of post-pandemic influenza antiviral resistance trends and highlights the growing relevance of PA-I38 variants, underscoring the need for continuous genomic surveillance and the development of next-generation antiviral strategies that target highly conserved viral functions.